KONTRIBUSI KOORDINASI MATA TANGAN DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP KETERAMPILAN LAY UP SHOOT PADA TIM BOLA BASKET PUTRI SMAN 9 PEKANBARU - Fizi, Resti Molina; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Problems in this study based on field observations on the SMAN 9 women's Basketball Team were seen in athletes when doing Lay Up Shoot. This study aims to examine whether there is a contribution of eye hand coordination and wrist flexibility in the Lay Up Shoot on the SMAN 9 Pekanbaru Women's Basketball Team. The sampling technique is the entire population (total sampling), amounting to 12 people. Based on the results of research conducted From the calculation of the analysis of the contribution of X and Y, it can be concluded that the contribution of hand eye coordination and wrist shape to the shoot lay up skills on the basketball team of the sman 9 Pekanbaru women's basketball, There is a contribution of 92.16% between eye coordination towards Lay Up Shoot skills. 2 people were 16.67%, 4 people were 33.33%, 1 person was in the category of 8.33%, and 8 people were 25%. There was a contribution of 56.25% between the flexibility of the wrist to the Lay Up Shoot skill. 4 people with 33.33%, 1 person with 8.33%, 5 people with 41.68% and 1 person with 8.33%. There was a contribution of 92.16% between eye hand coordination and wrist flexibility on the Lay Up Shoot skill. 4 people were 33.33%, 5 people were 41.6%, and 3 people were 25%.Key Words: Hand Eye Coordination, Wrist Flexion, Lay Up Shoot.